Effectiveness of Food Safety Education for Early Children's Health - Hermawati, Bertakalswa; Kartini, Apoina; Indarjo, Sofwan; Nugroho, Efa (Journal of Health Education, 2020)
Background: Diarrhea is a disease caused by food which is a health problem in early childhood. One cause is food that is not safe for consumption by children. Therefore it is important to educate mothers about the importance of managing food safety. The purpose of this study was to determine changes in maternal behavior after being given early childhood food safety education. Methods: This study uses a quantitative approach. with The One-Group Pretest-Posttest Design. The intervention given is education through film media and booklets. The instrument in this study was an early childhood food safety questionnaire with reference to three aspects namely maintaining cleanliness, preventing raw food from being consumed and preventing food from hazardous chemicals. This instrument is to measure changes in maternal behavior before and after the intervention. Sampling using a purposive sampling technique. The sample in this study was 57 mothers with children under five who were studying in kindergarten in Ungaran, Semarang district. Data analysis using the Wilcoxon test. Result: The results of this study prove that there was a significant increase in maternal behavior before and after food safety education intervention was given with a p-value of 0.020. Conclusion: There is a change in mother’s behavior in managing food safety for early childhood.